2021
DOI: 10.33096/jifa.v12i2.638
|View full text |Cite
|
Sign up to set email alerts
|

FORMULASI DAN EVALUASI FISIK SEDIAAN KAPSUL EKSTRAK DAUN CINCAU HIJAU (Cyclea barbata Miers ) SEBAGAI ANTI INFLAMASI

Abstract: One of the Indonesian plants that can be used is green grass jelly leaf (Cyclea barbata Miers) because it contains alkaloids, polyphenols, saponins and flavonoids that can prevent inflammation. Inflammation is an environmental physiological response caused by damage or damage to the tissue that functions, reduces, or confines an injuring agent or injured tissue. The purpose of this study was to formulate green grass jelly leaf extract into anti-inflammatory capsules. This research begins with the maceration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This recent study showed that pumpkin seed flour has a density of 0.2427 g/ml which means fulfilling the requirement for incompressible density >0.21 g/ml. 20 The flow time test was carried out to determine the time required for pumpkin seed flour to flow through the test equipment. To our best knowledge, it is the first study to examine flour flow from the seeds.…”
Section: Discussionmentioning
confidence: 99%
“…This recent study showed that pumpkin seed flour has a density of 0.2427 g/ml which means fulfilling the requirement for incompressible density >0.21 g/ml. 20 The flow time test was carried out to determine the time required for pumpkin seed flour to flow through the test equipment. To our best knowledge, it is the first study to examine flour flow from the seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a dose of 200 mg, 400 mg and Na-CMC are in different columns, indicating that the diarrhea value in each treatment was significantly different from the positive control group. 13 Furthermore, in the statistical test results in the column, the results of the frequency of diarrhea at a dose of 400 mg, a dose of 800 mg, Loperamide, a dose of 200 mg and Na-CMC were in the same column, concluding that the value of diarrhea in each of these treatments was not significantly different. The results of the loperamide stool weight at a dose of 800 mg, 200 mg, 400 mg and Na-CMC were in the same column, concluding that the value of diarrhea in each of these treatments was not significantly different.…”
Section: Alkaloidsmentioning
confidence: 92%